Outcomes of internal biliary diversion using cholecystocolostomy for patients with severe Alagille syndrome. Issue 7 (4th July 2022) - Durgin, Jonathan M; Crum, Robert; Kim, Heung Bae; Cuenca, Alex G
Abstract: Alagille syndrome (AGS) is a disorder that leads to increased serum cholesterol and bile acids, which can result in debilitating xanthomas and pruritus. External biliary drainage and transplantation are effective treatments for AGS. Internal biliary diversion with Roux-en-Y cholecystocolostomy has been described for other biliary conditions, but not AGS. Three patients with severe pruritus due to AGS underwent Roux-en-Y cholecystocolostomy for internal biliary drainage. Retrospective analysis compared preoperative and post-operative lab values and symptom scores (0, none–4, severe). Three patients underwent cholecystocolostomy. All patients had at least three diagnostic criteria for AGS. Mean preoperative pruritus score was 3.33 (range, 2–4) and mean post-operative score was 1. Mean preoperative xanthoma score was 1.33 (range, 0–4) and post-operative score was 1 at 2-month follow-up. Roux-en-Y cholecystocolostomy can be considered for AGS, which is refractory to medical management. This procedure accomplishes internal biliary diversion without significant physiologic derangements.